Electrical equivalent thermal network for direct contact membrane distillation modeling and analysis. (November 2016) - Karam, Ayman M.; Laleg-Kirati, Taous Meriem
Abstract : Highlights: We propose a novel dynamic model for direct contact membrane distillation process. The model is a reduced version of a distributed system. It is based on the analogy between electrical and thermal systems. The model has been validated with experimental data. The model is written in the form of differential algebraic system. Abstract: Membrane distillation (MD) is an emerging water desalination technology that offers several advantages compared to conventional desalination methods. Although progress has been made to model the physics of the process, there are two common limitations of existing models. Firstly, many of the models are based on the steady-state analysis of the process and secondly, some of the models are based on partial differential equations, which when discretized introduce many states which are not accessible in practice. This paper presents the derivation of a novel dynamic model, based on the analogy between electrical and thermal systems, for direct contact membrane distillation (DCMD). An analogous electrical thermal network is constructed and its elements are parameterized such that the response of the network models the DCMD process. The proposed model captures the spatial and temporal responses of the temperature distribution along the flow direction and is able to accurately predict the distilled water flux output. To demonstrate the adequacy of the proposed model, validation with time varying and steady-state experimental data is presented.